Risk factors for psychiatric disorders following traumatic brain injury: a multivariate logistic regression analysis - Liu, Hanyu; Yi, Tongjun (Frontiers in Psychiatry, 2024)
ObjectiveThis study aimed to investigate the incidence and risk factors of psychiatric disorders following traumatic brain injury (TBI).MethodsA total of 232 patients with closed TBI admitted to our hospital from January 2021 to January 2023 were included. Basic demographic data, injury circumstances, and psychiatric conditions during hospitalization were collected. Patients were followed up at 9 months post-injury, and based on clinical interviews, symptoms, and questionnaires, they were categorized into those with post-TBI psychiatric disorders and those without. The study aimed to explore the predictive factors for psychiatric disorders after TBI.ResultsAmong the 232 patients, 104 developed psychiatric disorders by the end of the 9-month follow-up, resulting in an incidence rate of 44.83%. The employment rate was significantly lower in the psychiatric disorder group compared to the non-psychiatric disorder group. Additionally, the GCS scores upon admission were significantly higher in the psychiatric disorder group, along with a greater proportion of limb injuries, post-traumatic coma, intracranial hematomas, and frontal lobe injuries. The results of the multivariate logistic regression analysis indicated that unemployment (caused by poor recovery from TBI), lower GCS scores at admission, limb injuries, post-traumatic coma, frontal lobe injuries, and the presence of psychiatric symptoms during hospitalization were independent predictors of psychiatric disorders following TBI.ConclusionUnemployment, lower GCS score on admission, limb injury, post-traumatic coma, frontal lobe injury, onset of psychiatric symptoms during hospitalization was identified as independent predictors of post-traumatic psychiatric disorders. Routine mental health screenings for conditions such as depression and anxiety should be integrated into the care of TBI patients.